Underutilization of prophylactic rectal indomethacin and pancreatic duct stent for prevention of post-ERCP Pancreatitis - Issak, Abdulfatah; Elangovan, Abbinaya; Ferguson, Roy D.; Waghray, Nisheet; Sandhu, Dalbir S. (Endoscopy International Open, 2021)
Background and study aims Incidence of Post-ERCP pancreatitis (PEP) ranges from 1 % to 10 % in unselected patients and as high as 25 % to 30 % in high-risk patients. Rectal indomethacin administered before or immediately after an ERCP and prophylactic pancreatic duct stent placement (PPS) are associated with a reduction in the incidence of PEP. We sought to investigate the utilization rate for prophylactic rectal indomethacin and PPS in average and high-risk patients undergoing ERCP between 2014 and 2019.Patients and methods We performed a retrospective analysis in the IBM Explorys database, a pooled, national de-identified clinical database of over 72 million unique patients from 26 health care networks and 300 hospitals across the United States from 2014 to 2019. Average and high-risk patients undergoing ERCP were identified using Systematized Nomenclature of Medicine Clinical Terms (SNOMED CT) diagnosis codes. PEP was defined by the presence of SNOMED CT diagnosis of acute pancreatitis and an inpatient admission within 5 days of an ERCP procedure. Results Out of 31,050 adults who had undergone ERCP from 2014 to 2019, only 10,500 individuals (33.8 %) had a PEP prophylaxis. Rectal indomethacin and PPS accounted for 82.4 % and 12.9 % respectively. Individuals with three risk factors had the highest PEP rates followed by individuals with two risk factors. Conclusions Only one-third of all patients undergoing ERCP received prophylaxis in the form of rectal indothemacin and/or PPS in this large population-based data. Increased implementation of prophylactic use is needed in patients undergoing ERCP as supported by current guidelines.